Youth developmental experiences among female hockey players: The role of relative age - Chittle, L.; Dixon, J. C.; Horton, S. (Journal of Youth Development, 2019)
Relative age differences can lead to varying sport participation opportunities; however, scant research has focused on the impact of relative age on experiences within sport. This study explored if youth developmental experiences differed by relative age among competitive female ice hockey players. Players within Ontario (n = 264) completed an online survey that contained the Youth Experience Survey for Sport (YES-S) along with additional demographic questions. The YES-S measures 5 dimensions of positive (i.e., personal and social skills, cognitive skills, goal setting, and initiative) and negative developmental experiences in sport. The results of the multivariate analysis of variance (MANOVA) suggested that the developmental experiences reported by athletes did not differ across birth quartiles (Wilks` Lambda = 0.940, F (15, 707.105) = 1.061, p = .390). Although there was a relative age effect (RAE) trend within this sample of competitive female ice hockey players, the differences across birth quartiles were not statistically significant. It appears that relative age does not result in youth having different positive and negative sporting experiences. Exploring the characteristics of sport environments (e.g., coaches, practices) and personality traits of competitive athletes to better understand how relatively younger athletes continue their participation in sport despite being at a perceived disadvantage warrants further investigation.